Enhanced anti−tumor efficacy of “IL−15 and CCL19” −secreting CAR−T cells in human glioblastoma orthotopic xenograft model - Chen, Wanqiong; Hong, Limian; Lin, Shaomei; Xian, Na; Yan, Cailing; Zhao, Ningning; Xiao, Yonglei; Liao, Wanting; Huang, Yuxiang; Chen, Mingzhu (Frontiers in Oncology, 2025)
Despite the remarkable success of CAR-T cell therapy in hematologic malignancies, its progress in solid tumors has been slow. Overcoming challenges such as the recruitment and infiltration of CAR-T cells into the tumor site and the survival issues in the harsh tumor microenvironment are crucial for successful application in solid tumors. In this study, CAR-T cells were engineered to secrete both IL-15 and CCL19, and their efficacy was evaluated in a human glioblastoma orthotopic xenograft model. The results reveal that 15 × 19 CAR-T cells exhibit superior proliferation, chemotaxis, and phenotypic characteristics compared to conventional CAR-T cells in vitro. In vivo, 15 × 19 CAR-T cells exhibit superior control over tumors compared to conventional counterparts. Mechanistically, the improved efficacy can be attributed, in part, to IL-15 and CCL19 enhancing T-cell infiltration at the tumor site and fortifying resistance to exhaustion within the tumor microenvironment. In conclusion, the incorporation of IL-15 and CCL19 into CAR-T cells emerges as a promising strategy to elevate the anti-tumor efficacy of CAR-T cell therapy, positioning 15 × 19 CAR-T cells as a potential breakthrough for enhancing the application of CAR-T therapy in solid tumors.